Climate transition risk in the banking sector: What can prudential regulation do? - Michael Grill; Alexandra Popescu; Elena Rancoita (European Central Bank (ECB), 2024)
Climate-related risks are due to increase in coming years and can pose serious threats to financial stability. This paper, by means of a DSGE model including heterogeneous firms and banks, financial frictions and prudential regulation, first shows the need of climate-related capital requirements in the existing prudential framework. Indeed, we find that without specific climate prudential policies, transition risk can generate excessive risk-taking by banks, which in turn increases the volatility of lending and output. We further show that relying on microprudential regulation alone would not be enough to account for the systemic dimension of transition risk. Implementing macroprudential policies in addition to microprudential regulation, leads to a Pareto improvement.
Keywords: D58; E58; E61; Q54; 330; transition risk; financial frictions; prudential regulation